(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Medications that are biosimilar are very similar to biologics that have been authorised by the FDA. When it comes to speciality treatment areas like immunology, endocrinology, and cancer, biosimilar medications might be helpful since the sponsors of premarket applications specify the product’s intended clinical use. Clinical therapies for individuals with potentially fatal disorders such cardiac myopathies, carcinoma, sarcoma, and lymphoma rely heavily on the newly authorised biosimilar drugs from the FDA. The pharmaceutical industry and regulatory agencies sought to supplant biologic medications that did not involve innovation with biologic pharmaceuticals that were comparable but did not. These pharmaceuticals are part of a new class called biosimilars, and their goal is to be exactly like the reference drug in terms of safety and effectiveness. Nocebo effects may restrict treatment adherence and induce unfavourable expectations, therefore it’s important for doctors and patients to be aware of this and work together to overcome it. The study’s intended participants were medical doctors, pharmacists, nurses, consultants, care managers, and oncologists, rheumatologists, endocrinologists, gastroenterologists, dermatologists, nephrologists, and hematologists, among other specialties.